INFORMATION ABOUT RADIO - Ahmedov , Azimjon Ilhomovich; Sobirova , Muniraxon (Educational Research in Universal Sciences, 2023)
Information about the radio who invited it, when including important milestones in the development of radio, past of prediction about the future radio.